Assessing Cognitive Bias in Forensic Decisions: A Review and Outlook. Issue 2 (6th November 2019) - Curley, Lee J.; Munro, James; Lages, Martin; MacLean, Rory; Murray, Jennifer
Abstract: In recent years, a number of studies have demonstrated that forensic examiners can be biased by task‐irrelevant contextual information. However, concerns relating to methodological flaws and ecological validity attenuate how much the current body of knowledge can be applied to real‐life operational settings. The current review takes a narrative approach to synthesizing the literature across forensic science. Further, the review considers three main issues: (i) primary research on contextual bias within forensic science; (ii) methodological criticisms of this research; (iii) an alternative perspective that task‐irrelevant contextual information does not always lead to error. One suggestion for future research is outlined, which is that studies on contextual bias in forensic decisions should be conducted in collaboration between forensic scientists and cognitive psychologists. Only then can rigorous and ecological valid experiments be created that will be able to assess how task‐irrelevant contextual information influences forensic analysis and judgments in operationally valid settings.